DEVELOPMENT OF DIGITAL D'SCRATCH MEDIA IN 21ST CENTURY LEARNING - Ahmad Fadillah; Dian Nopitasari; Westi Bilda (Prima: Jurnal Pendidikan Matematika, 2026)
This research aims to produce a valid and feasible scratch product for use in mathematics learning. The research was conducted using the Research & Development (R & D) method with the ADDIE model. Data collection techniques used validation questionnaires. The instruments used were in the form of validation questionnaires. The product validation results by media experts reached 82.5% and by learning experts 80%, categorized as very feasible for use. After the product was declared feasible and valid, the field test results by users showed an average score of 80.5%, with criteria of being very practical when used. The recommendation from this research is for teachers as a solution for 21st-century digital-based mathematics learning.